Water-Deficit Tolerance in Sweet Potato [Ipomoea batatas (L.) Lam.] by Foliar Application of Paclobutrazol: Role of Soluble Sugar and Free Proline - Yooyongwech, Suravoot; Samphumphuang, Thapanee; Tisarum, Rujira; Theerawitaya, Cattarin; Cha-um, Suriyan (Frontiers in Plant Science, 2017)
The objective of this study was to elevate water deficit tolerance by improving soluble sugar and free proline accumulation, photosynthetic pigment stabilization, photosynthetic abilities, growth performance and storage root yield in sweet potato cv. ‘Tainung 57’ using a foliar application of paclobutrazol (PBZ). The experiment followed a Completely Randomized Block Design with four concentrations of PBZ: 0 (control), 17, 34 and 51 M before exposure to 47.5% (well irrigation; WW), 32.3% (mild water deficit; MWD) or 17.5% (severe water deficit; SWD) soil water content. A sweet potato cultivar, ‘Japanese Yellow’, with water deficit tolerance attributes was the positive check in this study. Total soluble sugar content (sucrose, glucose and fructose) increased by 3.96 folds in ‘Tainung 57’ plants treated with 34 M PBZ grown under 32.3% soil water content (SWC) compared to the untreated plants, adjusting osmotic potential in the leaves and controlling stomatal closure (represented by stomatal conductance and transpiration rate). In addition, under the same treatment, free proline content (2.15 mol g-1 FW) increased by 3.84 folds when exposed to 17.5% SWC. PBZ had an improved effect on leaf size, vine length, photosynthetic pigment stability, chlorophyll fluorescence and net photosynthetic rate; hence, delaying wilting symptoms and maintaining storage root yield (26.93 g plant-1) at the harvesting stage. A positive relationship between photon yield of PSII (PSII) and net photosynthetic rate was demonstrated (r2 = 0.73). The study concludes that soluble sugar and free proline enrichment in PBZ-pretreated plants may play a critical role as major osmo-protectant to control leaf osmotic potential and stomatal closure when plants were subjected to low soil water content, therefore, maintaining the physiological and morphological characters as well as storage root yield.